2010
DOI: 10.1177/0047287509355327
|View full text |Cite
|
Sign up to set email alerts
|

Global Economic Crisis and Tourism: Consequences and Perspectives

Abstract: The International Academy for the Study of Tourism convened a session on global economic crisis and tourism during its 20th anniversary conference in Mallorca, Spain, in June 2009. Three articles featuring on the impacts of economic downturn on tourism in Asia and the Pacific, Europe, and North America have resulted and appeared in this issue of the Journal of Travel Research. This summary aims at an integrated discussion on the consequences and perspectives on the global economic crisis and tourism. The prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
166
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(185 citation statements)
references
References 9 publications
4
166
1
3
Order By: Relevance
“…The severe economic downturn and its subsequent climate of uncertainty tend to have a negative domino effect on tourism activities (Henderson, 2007;Papatheodorou and Xiao, 2010;Smeral, 2009 (Pizam, 2009). In parallel with this, the negative political scenery that prevails among certain European host countries is very likely to lead to negative tourist perceptions which in turn, can undermine demand and further decrease the number of arrivals at destinations (Pforr and Hosie, 2009).…”
Section: The Tourism-economic Growth Link In the Post-great Recessionmentioning
confidence: 99%
“…The severe economic downturn and its subsequent climate of uncertainty tend to have a negative domino effect on tourism activities (Henderson, 2007;Papatheodorou and Xiao, 2010;Smeral, 2009 (Pizam, 2009). In parallel with this, the negative political scenery that prevails among certain European host countries is very likely to lead to negative tourist perceptions which in turn, can undermine demand and further decrease the number of arrivals at destinations (Pforr and Hosie, 2009).…”
Section: The Tourism-economic Growth Link In the Post-great Recessionmentioning
confidence: 99%
“…Research has indicated a lack of willingness to reduce international, long-haul, travel behaviors (Higham and Cohen 2010;Cohen and Higham 2011). Nevertheless, societal changes including shifting travel and mobility patterns will have implications for tourist demands and could contribute to a greater number of ''staycations'' (Papatheodorou et al 2010). The social changes occurring as a result of climate change, and associated economic and political changes, will contribute to the vulnerability of a tourism destination.…”
Section: The Social Phenomenon Of Climate Changementioning
confidence: 99%
“…The GFC negatively impacted individual disposable incomes and job security leading to reduced international travel flows (Papatheodorou et al 2010;Ritchie et al 2010); this contributed to local-scale economic vulnerability in tourism destinations with low adaptive capacity (in this case a diversity of incoming tourist markets or non-tourism economic activities). This impact was not uniformly distributed; some regions indicated small degrees of impact.…”
Section: Economic Influencesmentioning
confidence: 99%
“…We hypothesized that TAID incidence rates may have decreased during the 2007-2009 economic recession due to decreased international travel, and thus, rates for before (1999-2006), during (2007-2009), and after the U.S. economic recession were compared. 7,14,15 Categorical variables were compared using χ 2 with Fisher's exact testing when appropriate.The 16 PHIS hospitals represented 2,203,063 pediatric hospital admissions during the study period. Individual and pooled cumulative TAID incidence trended upward from 1999 to 2012, though the trend did not achieve statistical significance (r 2 = 0.158).…”
mentioning
confidence: 99%
“…We hypothesized that TAID incidence rates may have decreased during the 2007-2009 economic recession due to decreased international travel, and thus, rates for before (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006), during (2007-2009), and after the U.S. economic recession were compared. 7,14,15 Categorical variables were compared using χ 2 with Fisher's exact testing when appropriate.…”
mentioning
confidence: 99%